2009
DOI: 10.1021/ie801853x
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactants from Urban Wastes As Auxiliaries for Textile Dyeing

Abstract: To promote biobased products for the industry, six biosurfactants isolated from green and food urban residues aged under aerobic digestion for 0−60 days were investigated for their potential to perform as auxiliaries for dyeing cellulose acetate fabric with water-insoluble dyes. The experimental plan included investigation of the chemical nature, surface activity, and power to enhance dye solubility in water, as well as dyeing test performed under a variety of experimental conditions presenting a range of chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
3
29
0
1
Order By: Relevance
“…[1] These substances act as promising chemical auxiliaries for major technological applications, for example, textile dyeing [2] and fabric washing, [3] where commercial synthetic surfactants are used.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1] These substances act as promising chemical auxiliaries for major technological applications, for example, textile dyeing [2] and fabric washing, [3] where commercial synthetic surfactants are used.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that BS110 was isolated from a biomass having a complex composition and subject to seasonal variation may raise concerns about the reproducibility of the BSs structure and thus of the properties of the templated materials derived from it. Despite this consideration, previous studies have shown that when the waste-derived biosurfactants were applied as active agents in detergent formulations [3] or as chemical auxiliaries in textile dyeing processes, [2] within certain limits, the chemical variability arising from their biological origin did not critically affect their performances. Nevertheless, to assess the variability of the BSs, the structural composition of BS110 was characterized in detail and compared to published BSs structures.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of both hydrophilic and hydrophobic functionalities forming the chemical structure of such BBS confers to these substances amphiphilic properties, as testified by the literature on analogous substrates [36][37][38]. As reported in our previous study [39], these BBS can be used in several industrial applications (as emulsifiers, foaming agents, in detergent formulations or as textiles auxiliaries, for the production of nanostructured materials, in animal husbandry, as fertilizers, or for the production of biofuels and bioplastics).…”
Section: Introductionmentioning
confidence: 63%